Acyl CoA synthetase 5 (ACSL5) ablation in mice increases energy expenditure and insulin sensitivity and delays fat absorption - Thomas A. Bowman; Kayleigh R. O'Keeffe; Theresa D'Aquila; Qing Wu Yan; John D. Griffin; Elizabeth A. Killion; Deanna M. Salter; Douglas G. Mashek; Kimberly K. Buhman; Andrew S. Greenberg (Elsevier, 2016)
Objective: The family of acyl-CoA synthetase enzymes (ACSL) activates fatty acids within cells to generate long chain fatty acyl CoA (FACoA). The differing metabolic fates of FACoAs such as incorporation into neutral lipids, phospholipids, and oxidation pathways are differentially regulated by the ACSL isoforms. In vitro studies have suggested a role for ACSL5 in triglyceride synthesis; however, we have limited understanding of the in vivo actions of this ACSL isoform. Methods: To elucidate the in vivo actions of ACSL5 we generated a line of mice in which ACSL5 expression was ablated in all tissues (ACSL5−/−). Results: Ablation of ACSL5 reduced ACSL activity by ∼80% in jejunal mucosa, ∼50% in liver, and ∼37% in brown adipose tissue lysates. Body composition studies revealed that ACSL5−/−, as compared to control ACSL5loxP/loxP, mice had significantly reduced fat mass and adipose fat pad weights. Indirect calorimetry studies demonstrated that ACSL5−/− had increased metabolic rates, and in the dark phase, increased respiratory quotient. In ACSL5−/− mice, fasting glucose and serum triglyceride were reduced; and insulin sensitivity was improved during an insulin tolerance test. Both hepatic mRNA (∼16-fold) and serum levels of fibroblast growth factor 21 (FGF21) (∼13-fold) were increased in ACSL5−/− as compared to ACSL5loxP/loxP. Consistent with increased FGF21 serum levels, uncoupling protein-1 gene (Ucp1) and PPAR-gamma coactivator 1-alpha gene (Pgc1α) transcript levels were increased in gonadal adipose tissue. To further evaluate ACSL5 function in intestine, mice were gavaged with an olive oil bolus; and the rate of triglyceride appearance in serum was found to be delayed in ACSL5−/− mice as compared to control mice. Conclusions: In summary, ACSL5−/− mice have increased hepatic and serum FGF21 levels, reduced adiposity, improved insulin sensitivity, increased energy expenditure and delayed triglyceride absorption. These studies suggest that ACSL5 is an important regulator of whole-body energy metabolism and ablation of ACSL5 may antagonize the development of obesity and insulin resistance. Keywords: Dietary fat absorption, Acyl-CoA, ACSL, Intestine, Liver, FGF21